Extraction methods and rheological behavior of Vietnamese Suong sao (Mesona Blumes Benth) gum - Trinh, Khanh Son; Nguyen, Thuy Linh (Old Journal, 2018)
Suong sao gum was prepared by different methods. Calcium sulafate or ethanol adding is necessary for a gel formation (sample CAS and ETH). Fourier transform infrared spectroscopy (FTIR) measurement indicating that suong sao gum contains xylan and LM pectin with various ratio. Base on gum concentration and shear rate, suong sao gum exhibits Newtonian fluid or pseudoplatic material. Besides, activation energy (Ea) of gums were from -15,71 to 23,02 (kJ/mol) reflecting their heat sensitivity and the increase of temperature resulting in the increase of viscosity. Furthermore, at pH 6-10 or adding sugars (glucose, sucrose) causes the increase in gum viscosity.